Sensors selection for tiles thermal performance test for poultry sheds (Research, Society and Development, 2020)
One of the biggest problems that Brazil faces in the production of eggs and broiler chicken is the climatic factor, because Brazil is a tropical country with inadequate climatic conditions for the production of the animals, making the performance of the birds less. Considering that in the present article, it is expected to be able to select sensors that, in the future, will confirm whether thermoacoustic tiles, replacing ceramic tiles or fiber cement tiles in legacy sheds, can bring better thermal comfort and reduce stress for laying hens , making it possible to increase egg production and decrease stressors. These low-cost sensors, produced for use with Arduino microcontrollers, were selected for comparison with a commercial datalogger. To check the relationship between the datalogger and the electronic sensors, scatter plots were constructed, comparing the readings of the measured sensors with the standard used, and the percentage of variance between the measured temperatures and humidity was evaluated. The correlation between the readings was evaluated based on the values of Pearson's linear correlation coefficients “r”. Sensors were chosen in which the means were equal, where the two-tailed critical t-test was less than the statistical t and as confirmed by the strong Pearson correlation. Thus, it was concluded that these chosen sensors can be used in a future experiment without major investments in dataloggers due to their proven equivalence.